Pengaruh Gaya Kepemimpinan, Lingkungan Kerja Melalui Disiplin Kerja terhadap Kinerja Karyawan JNE di Provinsi Jambi - Muhammad Oceano Fauzan (Universitas Batanghari, 2022)
In this study, the variables used were leadership style, work environment, work discipline and performance of JNE employees in Jambi Province. The purpose of this study is to provide input to JNE in Jambi Province and increase knowledge for readers. The research method used is by distributing questionnaires to JNE employees in Jambi Province, in answering the questionnaire respondents simply mark the column that has a Likert's Scale (1 – 5) above it. The results obtained from this study, partially leadership style (X1) and work environment (X2) on work discipline (Y) have a positive and significant influence both partially and simultaneously, then partially leadership style (X1) and work environment (X2 ) on performance (Z) has a positive and significant effect both partially and simultaneously, then the work discipline variable (Y) on performance (Z) has a positive and significant influence both partially and simultaneously, and simultaneously there is an influence between each variable.